The Effect of Vibration on the Acceleration of Wound Healing of Diabetic Neuropathic Foot Ulcer: A Prospective Experimental Study on Human Patients - Syabariyah, Sitti; Nurachmah, Elly; Widjojo, Budiman Darmo; Prasetyo, Sabarinah; Sanada, Hiromi; Irianto; Nakagami, Gojiro; Suriadi; Kardiatun, Tutur; Hisan, Urfa Khairatun (Healthcare (Basel), 2023)
Diabetic foot ulcers are a common complication that occurs in approximately 15 percent of patients with diabetes mellitus. Over 60% of diabetic foot ulcers are caused by underlying neuropathy. Former studies on diabetic animals with foot wounds found that vibration platforms significantly accelerate wound healing by catalyzing epithelization, promoting angiogenesis, and enhancing muscle bulk. This result suggests that there is evidence that vibrations may accelerate diabetic neuropathic ulcer healing in human patients. However, to the best of our knowledge, the effect of vibration on the enhancements of diabetic foot ulcer healing in human patients is rarely investigated. Hence, in this work, we conducted an experimental study with human subjects to investigate whether vibration therapy, as a complement to the standard wound treatment, can accelerate the wound healing rate of diabetic neuropathic foot ulcers. In this prospective experimental study, 80 participants diagnosed with Wagner grades I–III diabetic neuropathic foot ulcers were randomly distributed to experimental (n = 40) and control groups (n = 40). Patients in the intervention group received standard wound treatment and vibration wound therapy (VWT), whereas patients in the control group retrieved only standard wound treatment. The results (p = 0.024, α = 0.05) show notable differences in the median healing rate between the intervention group (25 days, 95% CI: 20.3–29.7) and control group (33 days, 95% CI: 25.6–40.4), with the effect-size r, Cohen’s d, Glass’s Δ, and Hedges’ g, respectively, being 0.810, 2.764, 2.311, and 2.772. Moreover, the nitric oxide (NO) level, wound closure area, and wound healing score after intervention significantly differed between the two groups (p < 0.05), putting the intervention group on a higher level than the control group. Furthermore, positive associations were found between the NO level and wound healing closure rates. These findings suggested that VWT enhances diabetic neuropathic foot ulcer healing in terms of healing rate, wound closure area, healing score, and elevated NO level. Considering that no clinically adverse effects were found in the patients induced with vibration intervention, VWT can be regarded as a complementary therapy to the existing ones to accelerate the healing of DFUs.